The Inactivation of Plasma-Thromboplastin - Deutsch, E; Mammen, E (Thrombosis and Haemostasis, 1958)
1. Anti-plasmathromboplastin activity is found in plasma and in serum.2. The anti-plasmathromboplastin activity was increased in the majority of patients with hemophilia A and B, with chronic idiopathic thrombocytopenia, uremia, and in the cases of obstetrical afibrinogenemia, obstructive jaundice and Morbus Addison examined. It was reduced in patients with hepatitis and with cirrhosis of the liver.3. The anti-plasmathromboplastin of serum is stable on storage; it is inactivated at temperatures over 60° C; it is partially adsorbed on the ion exchange resins ICR 50 and XE 64; it is not adsorbed on BaSO4, Al2O3, Al(OH)3, Kaolin and asbestos filter pads; its activity is increased after treatment with the ion exchange resin XE 88. It is not dialysable and not soluble in ether. It inactivates plasmathromboplastin gradually. After repeated additions of plasmathromboplastin its activity is exhausted.4. Two materials with anti-plasmathromboplastin activity could be separated by fractionation with ammonium sulfate, with ethanol or by changing the pH. These two materials differ in their physical properties and in their mode of action.Anti-plasmathromboplastin I is precipitated with 33% saturated ammonium sulfate, with 15% saturation with ethanol, or at pH 6.0; it is unstable on storage, it is inactivated at 70° C; it is partially adsorbed on the cation exchange resins XE 88 and ICR 50, and completely on XE 64. It inactivates plasmathromboplastin gradually. It is more stable, when oxygen is absent or cystein is added.Anti-plasmathromboplastin II remains in solution after 80% saturation with ammonium sulfate, 53.3% saturation with ethanol, or at pH 5.0. It is storage and heat stable; it is dialysable; it is not adsorbed on cation exchange resin ICR 50; its activity is increased by treatment with ion exchange resins XE 64 and XE 88. Its action is immediate,Both anti-plasmathromboplastins migrate with the α-globulin-fraction.5. The anti-plasmathromboplastin has no phosphatase activity. It does not inactivate platelet equivalents before they have reacted with plasma and serum factors to form plasmathromboplastin. Its action seems to be stoichiometric. The action is not influenced by calcium concentrations in a range from 3 to 14 mg%.6. The difference in the degree of inactivation of plasmathromboplastin with the use of our method as compared to the method of E g l i is due to the difference in the proportions of plasmathromboplastin and anti-plasmathromboplastin used in the tests.